Effect of anaerobiosis on the surface ultrastructure and surface proteins of Actinobacillus actinomycetemcomitans (Haemophilus actinomycetemcomitans). - Scannapieco, F A (1987)
The ultrastructures and surface protein profiles of aerobically cultured Actinobacillus actinomycetemcomitans (Haemophilus actinomycetemcomitans) differed from those of cells cultured anaerobically. Similar ultrastructural differences were also observed when aerobic and anaerobic cultures of a strain of Escherichia coli were compared. These results suggest that oxygen-related variations in the bacterial cell surface may play a role in the adaptation of oral bacteria to different host environments.